2023
DOI: 10.21273/horttech05238-23
|View full text |Cite
|
Sign up to set email alerts
|

Turfgrass Use on US Golf Courses

Abstract: Golf facilities account for 2.3 million acres in the United States. Numerous turfgrass species are managed on US golf facilities, but golf facilities may change turfgrasses depending on numerous variables. Knowing which turfgrasses are grown and how turfgrass selection has changed would provide important information to scientists, turfgrass managers, and policymakers. The objective of this survey was to measure turfgrass use on US golf facilities in 2021 and to determine whether changes in turfgrass selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…With the creation of 'Tifgreen', golf course managers saw the possibilities of having immaculate putting greens and fairways year-round. As indicated by a survey conducted in 2021, 32% of the total golf course acreage (80% of putting greens) in the southern United States adopted bermudagrass because of its stress tolerance and maintenance requirements (Emmons and Rossi 2015;Shaddox et al 2023), thus redefining what is possible for modern turf management. Bermudagrass can survive the scorching heat of the South and also performs extremely well at low mowing heights, leading to a consistent and visually pleasing golfing experience.…”
mentioning
confidence: 99%
“…With the creation of 'Tifgreen', golf course managers saw the possibilities of having immaculate putting greens and fairways year-round. As indicated by a survey conducted in 2021, 32% of the total golf course acreage (80% of putting greens) in the southern United States adopted bermudagrass because of its stress tolerance and maintenance requirements (Emmons and Rossi 2015;Shaddox et al 2023), thus redefining what is possible for modern turf management. Bermudagrass can survive the scorching heat of the South and also performs extremely well at low mowing heights, leading to a consistent and visually pleasing golfing experience.…”
mentioning
confidence: 99%
“…on golf courses (Jacobs 2019). There were > 159,284 ha of maintained bermudagrass on golf courses across the United States in 2021 that required regular mowing (Shaddox et al 2023b). Applications of imazapic as a PGR could assuage this issue.…”
mentioning
confidence: 99%
“…Although tolerance of common bermudagrass to imazapic for use as a PGR has been explored in the transition zone of the United States (Brosnan et al 2011), information pertaining to the response of hybrid bermudagrass (C. dactylon × Cynodon transvaalensis Burtt Davy) is lacking, considering the species constitutes 32% of all maintained turfgrass hectarage on golf courses (Shaddox et al 2023b). Limited research has demonstrated imazapic applications at 35 to 105 gÁha -1 reduced hybrid bermudagrass plant height > 28%, suggesting that it could be a tool to aid turfgrass managers in reducing mowing requirements on golf courses (Marques et al 2021b).…”
mentioning
confidence: 99%